Electro-acupuncture on Vascular Parkinsonism with multiple sleep disorders: A Case Report - Yan, Mingyue; Fan, Jingqi; Li, Yingjia; Liu, Xin; Yu, Zhengmiao; Zhuang, Lixing (Frontiers in Neurology, 2022)
Vascular Parkinsonism (VP) is a kind of rare secondary Parkinsonism caused by vascular lesions. Patients with VP experience not only movement disorders but also sleep disorders. But treatment options are limited and often associated with undesirable adverse effects. Electro-acupuncture (EA) is a safe, rapid work, easy operation, and convenient complementary replacement therapy. We report a case of a 51-year-old man who presented with VP and multiple sleep disorders. Based on clinical evaluation and nocturnal hospital-based polysomnography (PSG), the patient had severe PLMD (PSG showed severe periodic leg movements), excessive daytime sleepiness (EDS, the score of the ESS is 16), and probable rapid eye movement sleep disorder (RBD). Parkinson's disease sleep scale (PDSS) score, Pittsburgh sleep quality index (PSQI), and periodic leg movements index were 93, 11, and 135.2, respectively. After 8 weeks of EA treatment, the patient reported that the symptoms of subjective and objective sleep disturbance were significantly alleviated without any discomfort. This case report may provide a new alternative and complementary therapy for VP patients with sleep disturbance but more definitive and robust evidence is needed to support its efficacy.